ANALYSIS OF THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON NURSES' PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE DURING THE PANDEMIC COVID-19 AT JARAGA SASAMEH BUNTOK PUBLIC HOSPITAL - Raimona Anugerahny Narang; Anthonius Junianto Karsudjono (Jurnal Ekonomi, 2021)
Research purposes This is For know and analyze influence Motivation Work and Environment Work on Nurse Performance with Satisfaction Work as Intervening Variables during the COVID-19 Pandemic . Types of research This is study correlational use method descriptive and analytical track (Path Analysis) with approach quantitative . Variables independent consists of from motivation work and environment work , variable dependent that is performance nurses and variables his intervention that is satisfaction work . Samples used in study This use technique Proportionate Stratified Random Sampling of 96 people. Technique taking sample use formula Slovin. Data collection was carried out with method spread questionnaire , observation and interview direct . Data analysis techniques using analysis descriptive and analytical path ( path) Analysis) with help Smart PLS. Research results show that influence direct: (1) motivation Work influential positive and significant to satisfaction work; (2) environment Work influential positive and significant to satisfaction work; (3) motivation Work influential positive and significant to performance nurse; (4) environment Work influential positive and significant to performance nurse; (5) satisfaction Work influential positive and significant to performance nurse . While For influence No directly: (1) motivation Work influential positive and significant to performance nurse with satisfaction Work as intervening variables; (2) environment Work influential positive and significant to performance nurse with satisfaction Work as intervening variables at Jaraga Sasameh General Hospital Buntok.